12.4 THE BODILY SELF IN PSYCHOSIS: SENSORIMOTOR INDUCTION OF AUDITORY MISATTRIBUTION IN PSYCHOSIS IS LINKED TO NEURAL DISCONNECTIVITY. (9th April 2019) - Salomon, Roy; Progin, Pierre; Griffa, Alessandra; Rognini, Giulio; Do, Kim Q; Conus, Philippe; Marchesotti, Silvia; Bersconi, Fosco; Hagmann, Patric; Serino, Andrea; Blanke, Olaf
Abstract: Background: Psychosis is often depicted as a disruption of the self-model. Patients suffering from psychosis report many symptoms relating to deficiencies in the minimal self, including loss of the sense of control over their actions (Sense of Agency) as well as numerous disturbances of body representation (e.g. Body Ownership). Positive symptoms of psychosis such as passivity symptoms and auditory hallucinations (termed first-rank symptoms) are characterized by a diminished demarcation of self-other boundaries, causing misattribution of self-generated actions to external sources. It has been suggested that this deficiency in self-monitoring in schizophrenia is due to abnormal sensorimotor prediction mechanisms, causing a loss of agency for actions and thoughts. While the neurobiological underpinnings of schizophrenia are yet unclear, many studies have reported aberrant neural connectivity in schizophrenia patients which may impact sensorimotor prediction and integration. Methods: Recently, we have shown that introducing sensorimotor conflict (SMC) can induce psychosis like symptoms in healthy patients. Employing a master-slave robotic system we induced a conflict by introducing a delay between the participants' movements and the haptic feedback. The SMC caused a feeling of a Presence (FoP) which is a first rank symptom of psychosis. The FoP is also found in neurological patients with lesions in cortical regions of the temporoparietal cortex, insular cortex and fronto-parietal cortex related to abnormal bodily self-representation. Here, we tested if SMC may cause misattribution of auditory stimuli and if this is related to neural connectivity. We tested first episode psychosis patients (N=31) with and without first rank symptoms (related to the sense of control over actions and thoughts) as well as healthy participants (N=20) on an auditory attribution task while inducing conflict with the master-slave robot. Results: We found that when a SMC was introduced patients with first rank symptoms showed a decrease in their ability to judge if the auditory stimuli were in their own voice or the voice of another person. Resting state functional connectivity analysis indicated that the first rank patients had reduced connectivity in the network related to the SMC, but not in other control regions. Furthermore, the reduced functional connectivity correlated with the rates of auditory misattribution. Conclusions: Our results show that induction of SMC can cause auditory misattributions, and that this is related to reduced cortical communication in regions related to sensorimotor body representation. These findings connect two influential theories of psychosis linking cognitive theories of sensorimotor prediction error in schizophrenia with systems level theories of neural disconnectivity. Understanding these neurocognitive mechanisms underlying the disruption of the self-model in psychosis may allow novel approaches in early diagnosis and treatment of these conditions.